Histories of violence among clients seeking substance use disorder treatment: a systematic mapping review - Beeler, Sara; Gerrish, Olivia; Aldred, B. Grantham; Asher BlackDeer, Autumn (Frontiers in Psychiatry, 2024)
Introduction There is a limited literature base regarding the intersection of drug and alcohol treatment, violence, and trauma. While research substantiates that exposure to violence and trauma impacts the propensity to misuse substances, the conceptualization in clinical trials and practice has largely been narrow and gendered, referring only to intimate partner or domestic violence. Our systematic mapping review explored a more inclusive and expansive review of survivors of and perpetrators of violence and trauma (e.g., intimate partner violence, sexual assault, stalking, child abuse, political and community violence, criminal violence, micro violence, structural violence, and oppression) to establish: 1) the types of treatment settings included in intervention studies, 2) the common indicators of success or common outcomes recorded, and 3) understanding who is seeking treatment for drug and alcohol use with histories of violence. Methods A systematic mapping review was conducted to identify any peer-reviewed articles published from 2011 to 2022. The Web of Science database was searched using a broad set of Boolean search terms related to violence, substance use disorders, and treatment. Over 8,800 records were identified from the systematic review with a total of 48 articles meeting inclusion criteria. Results Most studies in this review included populations reporting perpetration of violence (n=23, 48%) versus participants reporting survival of trauma/violence (n=17, 35%). Results also indicated female identifying populations (n=19; 40%) were predominantly served, were treated in the US (n=33; 69%) and seen in an outpatient setting (n=24; 50%). Authors also were attentive to studies that included sexual and gender minorities and discovered only three studies (6%) explicitly acknowledging inclusion of transgender participants or participants in relationship with partners of the same sex; three more studies (6%) were focused on participants with histories of or engaging in sex work. Discussion This review outlines treatment and research implications directly situated in the gap of service delivery found in this review. Specifically, the results elucidate the impact on minoritized and excluded identities based on gender, sexual preference, criminal legal status and directions for research and treatment to increase inclusion, representation, and equity across research and treatment settings.